Interactive Math Path: Permainan Ular Tangga Berbasis Etnomatematika - Rani Puspita; Betty Kusumaningrum; Elfrida Yani; Kholifah Dinnisa; Krida Singgih Kuncoro; Annis Deshinta Ayuningtyas; Muhammad Irfan (Universitas Sarjanawiyata Tamansiswa, 2022)
This research is a learning media development research that aims to produce an online snake and ladder learning media